Developmental exposure to mepanipyrim induces locomotor hyperactivity in zebrafish (Danio rerio) larvae. (October 2020) - Shen, Chao; Zhou, Yixi; Tang, Chen; He, Chengyong; Zuo, Zhenghong
Abstract: Mepanipyrim is a widely used fungicide, and residues of mepanipyrim are frequently detected in commodities. However, the neurotoxicity and underlying mechanisms of mepanipyrim are still insufficiently understood. In this study, zebrafish embryos at 0.5–1.0 post-fertilization hours (hpf) were exposed to 0.1, 1, 10 and 100 μg/L mepanipyrim for 7 days. Our results showed that mepanipyrim could cause the locomotor hyperactivity and increase the concentration of γ-amino butyric acid (GABA) and the Na + /K + - and Ca 2+ -ATPase activities in zebrafish larvae. We have conducted the RNA-sequence and RT-qPCR to analyze the gene expressions. The mRNA expression levels of calcium/sodium ion conduction associated genes were observably up-regulated, demonstrating that mepanipyrim could enhance the cell energy metabolism, the synaptic transmission and skeletal muscle contraction, which were consistent with the locomotor hyperactivity. Meanwhile, exposure to mepanipyrim could significantly change the gene expression levels of gad1, bdnf, nlgn1, and type A and B GABA receptors in zebrafish larvae. This is the first study focusing on the underlying mechanisms of the neurotoxic effects that are induced by mepanipyrim. Graphical abstract: Image 1 Highlights: Mepanipyrim caused the locomotor hyperactivity in zebrafish larvae. Mepanipyrim increased Na + /K + - and Ca 2+ -ATPase activities. Mepanipyrim changed the GABA content of the larvae. Mepanipyrim changed the gene expression levels of gad1, bdnf, nlgn1, and type A and B GABA receptors.